The public health CARES initiative: a framework for public health education in high schools using the SMAART model - Joshi, Ashish; Jha, Niharika; Taylor, Michelle; Saulsberry-Scarboro, Nichole; Orians, Courtney; Parish, Sally; Johnson, Kristle Hodges; Ward, Lori; Entwistle, Coree; Kedia, Satish; Russomanno, David (Frontiers in Public Health, 2025)
Using the SMAART model (Sustainable, Multisector, Accessible, Affordable, Reimbursable, and Tailored), the Public Health CARES [Coping, Adaptability, Resilience, Empathy, and Success, (or PH-CARES)] initiative aims to address health inequities among youth to promote health education in schools and communities. PH-CARES integrates public health curriculum into high schools to enhance students’ knowledge and skills, fostering their adaptability, resilience, empathy, and success. The PH-CARES initiative includes the establishment of a public health dual-enrollment program, Public Health Clubs, and the Public Health Hackathon, all designed to provide hands-on learning experiences. Our preliminary assessments from these initiatives reveal that they bridged didactic learning to real-world applications and facilitate students’ engagement with public health campaigns, community projects, and case studies, while providing the opportunity to earn college credits through a dual-enrollment program. Students participating in these initiatives gained a deeper understanding of public health issues, population health, social determinants, and data analytics, and were sensitized to local health issues preparing them for future public health careers. The initiative’s holistic approach demonstrates the potential for scalable public health education programs that empower students and promote long-term community health and well-being, establishing a model that can be implemented globally.